Inhibition of quorum sensing by compounds from two Eunicea species and synthetic saturated alkylglycerols - BARRAGÁN A., Clara; SILVA G., Edelberto; MORENO M., Bárbara; MAYORGA W., Humberto (Vitae, 2018)
Background: the emergence of bacterial resistance has led to a search for new natural products as alternatives starting points to prevent and control diseases caused by microorganisms. Among the potential candidates were bioactive compounds from octocorals of the genus Eunicea due to their chemical structures and their wide range of biological activities. Objective: the purpose of this study was to evaluate the quorum sensing inhibition (QSI) and antibacterial activity of compounds previously isolated from two Eunicea species and synthesized alkylglycerols (AKG). Methods: the QSI of three nonpolar compounds and a mixture of AKGs from Eunicea were evaluated by a microtiter plate assay using Chromobacterium violaceum (ATCC 31532). Four naturally occurring, saturated, and enantiomerically pure AKGs, all of which were derived from the chiral precursor (R)-solketal, were synthesized from alkyl chains of 12, 14, 16 and 18 carbons, and their structures were spectroscopically verified by NMR, ESI-MS and optical rotation data. Their QSI by the disc diffusion assay and minimum inhibitory concentrations (MIC) against 14 clinical bacterial isolates in microtiter plates were determined. Results: cembradiene 1, the AKG mixture and AKG (2S)-3-O-dodecyl-1,2-propanediol 4 inhibit QS at the same concentration as kojic acid (10 µg/well or 20 µg/disc, respectively). In this study, the bioactive compounds 1, stearyl oleate 2, acylglycerol 3 and AKGs 4 and (2S)-3-O-tetradecyl-1,2-propanediol 5 showed in vitro IQS activity for the first time. Additionally, 4 and 5 displayed in vitro antibacterial activity against Listeria innocua and Staphylococcus aureus (MIC = 32 µg/mL for both 4 and 5), Enterococcus faecalis (128 µg/mL and 64 µg/mL respectively), Micrococcus luteus (128 µg/mL for both) and Brevibacillus brevis (Bacillus brevis) (512 µg/mL and 64 µg/mL respectively). Conclusion: results suggest that natural compounds 1, 2, 3, 4 and 5 showed QSI, also 4 and 5 have antibacterial activity and they are an interesting alternative to continue researching their effect against pathogenic microorganisms.